Examining support for the rights of Indigenous Peoples in the context of REDD+ in Peru - Rodríguez, S.; Sarmiento Barletti, J.P.; Larson, A.M. (CIFOR-ICRAF, 2022)
Safeguard interpretation processes depend on national interpretations of relevant laws and recognized rights, including adherence to international agreements on the rights of Indigenous Peoples and local communities (IPLCs) and different political and economic priorities.